Resident Perceptions of Tourism at Eleko Beach, Nigeria - BAMIRO, Babasola; DIGUN-AWETO, Oghenetejiri (Journal of Environmental Management and Tourism; Vol 11 No 6 (2020): JEMT Volume XI, Issue 6(46) Fall 2020DO - 10.14505/jemt.v11.6(46).06, 2020)
An understanding of the perceptions of residents about the impacts of tourism helps planners maximize positive benefits and minimize the negative impacts the industry inevitably has. This study investigates the perception of residents in a local community in a developing country Nigeria, trying to understand whether the predominant perceptions are positive or negative. Questionnaire-based primary research was used to measure the attitudes and opinions of residents to different statements of positive and negative impacts and general support for the industry. The results show that the predominant perceptions in the community are positive ones and that there were significant relationships between the demographics data obtained and some perceptions and also that resident’s economic dependence affects how people felt either positively or negatively and their perceptions of the industry affect their support of the industry.